Sikap masyarakat terhadap penyandang disabilitas: faktor jenis kelamin, usia, dan tingkat pendidikan - Amaliah, Amaliah; Rasnah, Karlina Dieka; Rachmayanti, Ratu Indah; Hibatullah, Najib; Musayaroh, Siti (Literal: Disability Studies Journal, 2024)
The presence of people with disability in society is part of the society itself, so the involvement of them in community life needs attention from those around them. This study analyze the attitudes of society towards people with disability. A total of 69 respondents completed a sentiment scale questionnaire, with the highest score indicating a negative attitude towards people with disability. The questionnaire consisted of 14 questions with a Likert scale from 1 (strongly disagree) to 5 (strongly agree). Data were analyzed using non-parametric statistics (Spearman correlation coefficient) and multiple regression analysis. The results show that the general attitude of society towards people with disability is positive (M = 2.50). Age and level of education variables show an inverse correlation, indicating that as age and education level of the society increase, the attitude towards disability people also increases. Females have a more positive attitude towards people with disability compared to males.